An e-healthcare authentication protocol employing cloud computing. (23rd March 2021) - Mohit, Prerna; Amin, Ruhul; Biswas, G.P.
Telecare medical information system (TMIS) provides a wide array of medical information to the respective participants (doctor/patient) over insecure networks. The patient medical data is extremely sensitive and confidential along with authentication. This paper presents an architecture for e-healthcare using TMIS system employing a cloud server to store the medical information of registered patients. In addition, the proposed secure authentication protocol comprises a mobile device to ensure secure communication between the participants and contributes a platform for proper communication. To proof authenticity, both formal and informal security analyses have been successfully executed to resist attacks. Moreover, the computation and communication costs of the reported scheme offered better results in comparison to existing literature.